2021
DOI: 10.1002/chem.202100691
|View full text |Cite
|
Sign up to set email alerts
|

Two‐Dimensional Guanidine‐Based Hybrid Perovskites with Strong Dichroism for Multiwavelength Polarization‐Sensitive Detection

Abstract: Two-dimensional (2D) organic-inorganic hybrid perovskites, benefiting from their natural anisotropy of quantum-well motifs and optical properties, have shown remarkable polarization-dependent responses superior to the 3D counterparts. Here, for the first time, multiwavelength polarization-sensitive detectors were fabricated by using single crystals of a guanidine-based 2D hybrid perovskite, (BA) 2 (GA)Pb 2 I 7 (where BA + is n-butylammonium and GA + is guanidium). Its unique 2D quantum-well structure results i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 51 publications
(105 reference statements)
1
2
0
Order By: Relevance
“…This finding indicates that polarization-sensitive photodetection primarily originates from structure-induced polarization-dependent light absorption. Remarkably, both the P and LDR abs metrics outperform those reported in previous organic PSPs, to the best of our knowledge (refer to Figure a). ,,, We have depicted a clear polarization dependency of the photocurrent in Figure S16, ESI, and have plotted the corresponding angle-resolved normalized photocurrent curve in polar coordinates (Figure b). The photocurrent exhibits a peak when the polarization aligns with the c axial direction of the DTT-8 crystals and diminishes with an increase in the polarization angle, reaching a valley when perpendicular to the b axial direction.…”
Section: Resultssupporting
confidence: 57%
“…This finding indicates that polarization-sensitive photodetection primarily originates from structure-induced polarization-dependent light absorption. Remarkably, both the P and LDR abs metrics outperform those reported in previous organic PSPs, to the best of our knowledge (refer to Figure a). ,,, We have depicted a clear polarization dependency of the photocurrent in Figure S16, ESI, and have plotted the corresponding angle-resolved normalized photocurrent curve in polar coordinates (Figure b). The photocurrent exhibits a peak when the polarization aligns with the c axial direction of the DTT-8 crystals and diminishes with an increase in the polarization angle, reaching a valley when perpendicular to the b axial direction.…”
Section: Resultssupporting
confidence: 57%
“…The photodetector based on (BA)2(GA)Pb2I7 (Fig. 29a) has obvious anisotropic photocurrent in some different wavelengths of the visible band 876 . The PdSe2-based device, shown in Fig.…”
Section: D Polarization-sensitive Photodetectorsmentioning
confidence: 99%
“…Low-dimensional structures, especially one-dimensional (1D) and two-dimensional (2D) structures, are also anisotropic atomic structures that could produce interesting anisotropies, such as anisotropic electronic structure, anisotropic carrier transport, and birefringence. Recently, examples of low-dimensional perovskite materials have shown linear dichroism behaviors and outstanding anisotropic properties and exhibited more promising applications in polarized luminescence, polarized photon detection, and optical modulation. As is known, the large single crystals have a minimal number of grain boundaries and fewer structural defects and therefore usually lead to enhanced performance. , Several 2D hybrid perovskite single crystals have been synthesized recently, showing excellent anisotropic photonic performance. , Recently, Zhang et al reported centimeter-sized 1D perovskite ( n -propylammonium)­(methylammonium)­SbBr 5 single crystals with excellent linear dichroic anisotropy . However, reports of large 1D perovskite single crystals have been limited, and the corresponding anisotropic property has therefore also not been demonstrated.…”
mentioning
confidence: 99%